Repositioning NAHCON for Excellence in Hajj Management: A Strategic Framework for Enhanced Governance, Transparency, and Pilgrim-Centric Service Delivery - Aliyu Ibrahim Musaddad; Ismaila Yusuf Usman; Darania Anisa (Journal of Economic Studies, 2026)
The Nigerian Hajj Commission (NAHCON) plays a pivotal role in ensuring seamless pilgrim experiences. However, persistent challenges in governance, transparency, and service delivery underscore the need for transformative reforms. This study leverages existing literature, policy documents, and international best practices to develop a strategic framework for NAHCON’s excellence in Hajj management, aligning with the United Nations’ Sustainable Development Goals (SDGs). A comprehensive review of NAHCON’s mandate, structure, and operations identifies governance gaps, transparency bottlenecks, and service delivery inefficiencies. Comparative case studies of leading Hajj management authorities (e.g., Saudi Arabia’s Hajj Ministry, Malaysia’s Tabung Haji) inform the development of a tailored strategic framework that integrates: Enhanced Governance Structures: Board restructuring and professionalization, Transparency Mechanisms: Real-time reporting and e-governance platforms, Pilgrim-Centric Services: Customized packages and digitalized processes. The framework is designed to boost NAHCON’s institutional capacity, improve pilgrim satisfaction, and position Nigeria as a leader in global Hajj management. Policymakers, Hajj authorities, and development partners will find this research instrumental in shaping inclusive, accountable, and efficient Hajj systems.